Multipliers of Fourier-Haar Series in Lorentz Spaces - Tleukhanova, Nazerke; Bashirova, Anar (Eurasian Mathematical Journal, 2022)
This article provides a complete description of the multipliers of the Fourier series along the Haar system in the Lorentz spaces \(L_{p,r}\). Necessary and sufficient conditions are obtained ensuring that \(\{λ_k^j\}_{k=0,j=1}^{∞,2^k} \in m(L_{p,r} → L_{q,s})\). This work generalizes and supplements the result of work [8].